ANALISIS KOMPLEKSITAS SISTEM ORGANISASI DAN SISTEM INFORMASI PENJUALAN PD ASIAPHONE - Kristina Kristina (INTEKSIS, 2021)
Information systems are a very broad field of science because they exist in all areas of human life. Examples of areas of human life such as health, education, geography, politics and so on are in dire need of a clearly mapped information system so that it can run well. In mapping the information system in the organization's system requires good methods such as benefit methods, activity decomposition and resource allocation, recording, processing, recording and reporting activities. In addition, the boundaries between organizational systems and information systems must be clarified so that the design of software supporting information systems can be developed objectively according to needs. The complexity of organizational systems and information systems must be clearly mapped in one analysis document so that it can be used as a foundation for building software systems that support computerization of information systems for the organization's systems. In addition, the analysis document is also the basis for building the database system and network system. The skill of mapping the complexity of organizational systems and information systems can be started by understanding the specific methods that are intended for the complexity analysis activities. Sensor Signal Processing Indicator Diagrams are used to map the complexity of organizational systems and information systems with clear boundaries and problem definitions. Keywords : Organizationa, Information, System, boundaries